Peran Guru dalam Membangun Pendidikan Karakter Melalui Nilai-Nilai Pancasila di Era Society 5.0 - Nuzul Rohmah; Annisa Bella Puspita; Nungky Fitria Widyastuti; Supriyadi; Amrina Izzatika (Lembaga Intelektual Muda (LIM) Maluku, 2024)
In the era of Society 5.0, technological developments have become an inseparable part of everyday life, which has a major influence on various sectors, including education. The challenges of globalization and digitalization require character building based on Pancasila values among students. Teachers play a strategic role in instilling and developing Pancasila values by integrating technology into the teaching and learning process. This study aims to investigate the role of teachers in building student character based on Pancasila in the era of Society 5.0. This research is a study that uses a library research type with a qualitative approach, and data is collected through documentation methods. The results of the study indicate the importance of teachers adapting to technology and implementing innovative teaching methods to strengthen the internalization of Pancasila values in students. In addition to functioning as educators, teachers also act as role models and facilitators in facing moral and social challenges in the digital era. In conclusion, the importance of the role of teachers in instilling and fostering values through character education for students in the era of Society 5.0 must be in line with the times so that various problems can be overcome in character education